2019
DOI: 10.30607/kvj.594550
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Sox2, ß-III Tubulin and Nestin Expressions in Neuropsheres Differentiated from Bovine Adipose Derived Mesenchymal Stem Cells by Immunofluorescence Staining

Abstract: Stem cell therapy can be an advantageous tool for non treatable diseases and has become a theme research for a better solution to many neurodegenerative cases. Despite of being very common in pet animals and equines in the field of veterinary medicine; stem cell based practises in bovines yet remain very limited. In the following study, Bovine adipose derived stem cells (BASCs) were isolated and differentiated into neurospheres. The potential expressions of neuron-specific markers β-III Tubulin, Nestin and Sox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
2
2
0
Order By: Relevance
“…Adipogenic differentiation was proved by Oil red-O to detect intracellular lipid droplets ensuring that the cells differentiated into adipogenic lineage. These findings and procedures were similar to previous studies in this regard (Koç et al 2008, Moonesi Rad et al 2019, Fink and Zachar 2011, Nawaz et al 2020, Ozden-Akkaya et al 2019. Furthermore, neurospheres generation from adipose tissue make provision for the treatment of alleviation of neurogenic disorder or diseases that may need proper administration media and process.…”
Section: Discussionsupporting
confidence: 88%
“…Adipogenic differentiation was proved by Oil red-O to detect intracellular lipid droplets ensuring that the cells differentiated into adipogenic lineage. These findings and procedures were similar to previous studies in this regard (Koç et al 2008, Moonesi Rad et al 2019, Fink and Zachar 2011, Nawaz et al 2020, Ozden-Akkaya et al 2019. Furthermore, neurospheres generation from adipose tissue make provision for the treatment of alleviation of neurogenic disorder or diseases that may need proper administration media and process.…”
Section: Discussionsupporting
confidence: 88%
“…Therefore, investigating as much stem cell source as we can could point out the best source and approach for the intended use of neurospheres. Previous attempts on neurospheres generation from bovine stem cells were performed using bovine adipose tissue derived stem cells and bovine amniotic fluid derived stem cells under serum-free induction conditions by our team, and in both studies similar to the current research, all the neurospheres were positive against Sox2, Nestin and ß-III Tubulin protein expressions (Akkaya et al, 2019;Nawaz et al, 2020). Yet, a previous neurogenic attempt made by Dueñas et al (2014) using β-mercaptoethanol treatments on bovine BM-MSCs could not lead to successful expression of neural stem cell markers like Nestin and MAP2.…”
Section: Discussionsupporting
confidence: 79%
“…As all in vivo applications require the serum-free inoculation of stem cells and their derivatives, testing a serum-free approach for generating neurospheres is crucial for road mapping the futuristic approaches in the same area. With this point of view, we previously tested the potential of bovine adipose derived stem cells (Akkaya et al, 2019) and amniotic fluid derived stem cells (Nawaz et al, 2020) to generate Sox2 and ß-III Tubulin positive neurospheres using serum-free induction medium. In this study, an another source was used as bovine bone marrow derived mesenchymal stem cells were isolated.…”
Section: Introductionmentioning
confidence: 99%
“…Other studied found that in vitro -induced neurospheres derived from hDPSCs expressed Nestin, 13 , 17 and that neurospheres derived from stem cells of bovine adipose tissue expressed Nestin, SOX2, and β-III tubulin (neurogenic-associated protein). 43 Moreover, it was found that in vivo NSCs derived from neurospheres of embryonic brain cells E14.5 to E16.5 were positive for Nestin staining, thus confirming their NSC properties. 44 The neurospheres analyzed in the present study consisted of a heterogeneous population with different immunofluorescence staining patterns, and the co-expression of Nestin and SOX2 in the intra-neurospheral cells verified their profiling as NSC.…”
Section: Discussionmentioning
confidence: 82%